Faba Bean (Vicia faba L.) - Abou-Khater, Lynn; Balech, Rind; Maalouf, Fouad (CABI, 2025)
Faba bean (Vicia faba L.) is an important cool season food legume, rich in protein and essential micronutrients. It plays a critical role in improving land structure and contributing to wild pollinator maintenance. It was domesticated in the Fertile Crescent of the Near East and spread to more than 60 countries with diverse agroecology around the world. Despite its nutritional value and adaptability, faba bean cultivation faces challenges, including biotic and abiotic stresses, reducing cultivation areas in various countries. Conservation efforts, notably by organizations like the ICARDA Gene Bank, have preserved diverse genetic resources, ensuring the genetic resilience of this valuable crop. These genetic repositories are invaluable for breeding programmes, enabling the development of high-yielding and stress-resistant varieties. Despite the historical limited funding provided to faba bean, the research on crop improvement and agronomy led to a substantial increase in its yield. Moreover, to achieve higher productivity in the farming field, modern tools were developed to ensure higher genetic gains and faster release of cultivars. These include speed breeding with four generations per year, and the discoveries of single nucleotide polymorphism markers which are key achievements towards the development of marker-assisted selection techniques.